Aboriginal peoples and Section 25 of the Canadian Charter of Rights and Freedoms - Wildsmith, Bruce H. (University of Saskatchewan Native Law Centre, 1988)
This study analyzes conflicts arising from section 25 of the Canadian Charter of Rights and Freedoms with regard to aboriginal (Indian, Eskimo and Metis) rights and freedoms already guaranteed them by previous acts and treaties.